Penerapan Algoritma Kriptografi ElGamal untuk Pengaman File Citra - Tamam, M. Taufiq; Dwiono, Wakhyu; Hartanto, Tri (Fakultas Teknik, Universitas Brawijaya, 2012)
Abstract - Application security system image file is created in this research using ElGamal cryptographic algorithms and compiler program used is Borland Delphi 7. ElGamal cryptography algorithm is one of the key asymmetric cryptographic algorithm that uses a different key pair, an encryption key and a decryption key. Results from these applications can encrypt a bitmap image file type with 24-bit pixel format. Image generated using the extension